LGBT IN THE PERSPECTIVE OF HADITH: THEMATIC ANALYSIS AND IMPLEMENTATION OF PREVENTIVE MEASURES - Ahmad Ghazali Ibnu Syifa; Muhammad Asgar Muzakki; Muhammad Ghifari (Fakultas Agama Islam, Universitas Islam As-Syafiiyah, 2024)
The study aims to analyze the hadiths associated with the LGBT phenomenon and to identify preventive efforts that can be taken to address this problem among modern Muslims. The research method used is a qualitative approach to data collection techniques through library study. The hadiths analyzed include Islamic views on LGBT behavior and related sanctions. In addition, the study also reviews preventive measures that have been implemented in various Muslim communities to deal with this phenomenon, including religious education, counselling, and rehabilitation programmes. The findings show that a deep understanding of LGBT-related hadiths as well as a holistic and empathic approach to religious education and guidance can help reduce the prevalence of the LGBT behavior among modern Muslims. This research is expected to contribute to the development of effective strategies in tackling the LGBT phenomenon in accordance with the teachings of Islam